Nalar Moderat Istinbat Al-Ahkam Nahdlatul Ulama - Syafi'i, Imam (Proceedings of Annual Conference for Muslim Scholars, 2022)
Islamic law or fiqh is ineffective in responding to legal problems that are happening in society if the tools of the ijtihad or istinbāṭ al-aḥkām process are ignored. The rule “changes in law due to changes in times, places, and conditions” emphasizes the development of law. Therefore, the development of the istinbāṭ al-aḥkām methodology and reforms need to be carried out to be able to accommodate human problems as logical demands in the reality of life. This study examines the dynamics of making legal decisions by Nahdlatul Ulama (NU) in responding to contemporary problems in Indonesia. With a qualitative approach and library research, researchers will examine various sources, both primary and secondary, contained in various decisions of the National Deliberation and NU General Conference, journals, books and other research results. The 1992 National Deliberation in Bandar Lampung was the basic foundation of the law-making system for NU, it was explained that the law-taking procedure was within the framework of being based on one of the four agreed schools of thought and prioritizing the Qauli school of thought. If it is not found either qauliy or ilhaq, then it is carried out according to the Manhajiy school of thought. The next generation of Ulama make explanations (syarah) in stages, at the 2015 Muktamar deciding on the istinbāṭ Jamā'iy Mechanism, the 2017 National Deliberation deciding on the Taqrīr and Ilhāq Jamā'i Mechanisms, and the 2021 National Conference deciding on the istinbāṭ Maqashidi Mechanism or istinbāṭ Istishlahi . From these dynamics, it is emphasized that NU has a moderate principle where the law continues to develop and strengthens that Islamic law is flexible, elastic and dynamic so that it is adaptive to space and time.